Transactions on Engineering Technologies International MultiConference of Engineers and Computer Scientists 2016 - Ao, Sio-Iong.; Kim, Haeng Kon.; Huang, Xu.; Castillo, Oscar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This volume contains selected revised and extended research articles written by prominent researchers who participated in the International MultiConference of Engineers and Computer Scientists 2016, held in Hong Kong, 16-18 March 2016. Topics covered include engineering physics, communications systems, control theory, automation, engineering mathematics, scientific computing, electrical engineering, and industrial applications. The book showcases the tremendous advances in engineering technologies and applications, and also serves as an excellent reference work for researchers and graduate students working on engineering technologies, physical sciences and their applications.
Chapter 1. Pose Estimation of Mobile Robots Using Floor-Installed RFID Tags -- Chapter 2. Solution of differential flat systems unising variational calculus -- Chapter 3. High Performance Fully Adaptive Runtime Thermal-Aware Routing Algorithm for 3D NOC -- Chapter 4. PUF-based Protocols about Mutual Authentication and Ownership Transfer for RFID Gen2 v2 Systems -- Chapter 5. College Students' Online Purchase Intention in Big Data Era -- Chapter 6. Door Monitoring System Using Sensor Node with Zero Standby Power -- Chapter 7. The Wireless Obstacle Detection Based on Kalman Filtering for Vehicle-Teleoperation -- Chapter 8. Mining Attribute-specific Ratings from Reviews of Cosmetic Products -- Chapter 9. Utilizing Various User Moods for Automatic Recipe-Metadata Generation -- Chapter 10. Performance Analysis of Proprietary and non Proprietary Tools for Industry Based Regression Testing Using IIGRTCP Algorithm -- Chapter 11. Interactive Decision Making for Multiobjective Simple Recourse Programming Problems with Discrete or Continuous Fuzzy Random Variables.-.
Keywords: Industrial engineering; Production engineering; Mathematical models; Software engineering; Computer networks .; Control engineering; Robotics; Automation; Computer vision; Industrial and Production Engineering; Mathematical Modeling and Industrial Mathematics; Software Engineering; Computer Communication Networks; Control, Robotics, Automation; Computer Vision